Deducting the Cost of Sex Reassignment Surgery: How O’Donnabhain v. Commissioner Can Help Us Make Sense of the Medical Expense Deduction - Luszti, Tamar E. (Columbia Journal of Tax Law, 2012)
In February 2010, the Tax Court held that a taxpayer’s expenses incurred for hormone therapy and sex reassignment surgery were deductible as medical expenses under § 213 because they treated the disease of gender identity disorder. The court, however, was deeply divided in its determination of whether sex reassignment surgery qualifies as nondeductible cosmetic surgery under § 213(d)(9). In 1990, Congress amended § 213 to exclude cosmetic surgery from the definition of deductible medical care. Since then, the Tax Court and the I.R.S. have rarely addressed the meaning and extent of that exclusion. The judges’ divergent opinions in O’Donnabhain make it clear that a thorough examination of the statutory meaning of cosmetic surgery is timely. This Note considers what should qualify as cosmetic surgery within the context of the medical expense deduction. It argues that a medical procedure that improves physical appearance should be deductible under § 213 when it is physician-prescribed treatment for a specific disease, and consistent with generally accepted medical practice. This analysis is grounded in the statutory language of § 213, and is supported by broader principles that bear on the policy debate surrounding the medical expense deduction more generally.